Interviews to Dublin Core Application Profiles developers - Malta, Mariana Curado (2013)
These files are the recordings and transcripts of 3 interviews made to 3 Dublin Core Application Profiles developers with the aim to understand the process of a DCAP development. These interviews are framed in a PhD project that has as goal the definition of a method for the development of Dublin Core Aplication Profiles. An Application Profile is a construct on the Semantic Web that enhances interoperability.